O uso das redes sociais online nas interações de produtores e receptores de televisão - Marques, Paula Cecília de Miranda; Médola, Ana Sílvia Lopes Davi [UNESP] (My University, 2014)
This paper discusses the possibility of receiver’s participation in the production of television content mediated by online social networks. Buoyed by media convergence, this research demonstrates how the receiver has been working in online digital media such as TV can take advantage of the specific interaction between the medias to promote the creation of collaborative content, in which the user of social network may interfere the result of the product developed, becoming a new mediatic protagonist. Tool not so used for the production of television that slowly begins to enter the virtual reality, the forging of this new compose process would not only entertain the receiver, but also enrich the language and content television constantly criticized. This study shows the influence of the television medium in which is discussed online, the attitude still shy of the user in content production, and discusses the potential of social networks as a channel of communication between producers and receivers. This work is structured from the definition of social network, in addition to conducting the study what kind of interaction between TV and online social networks is practiced today. Finally, debate whether the potential interaction between TV and social networks is used to its fullest.

Este artigo trata da possibilidade de participação do receptor na produção do conteúdo televisivo intermediada por redes sociais online. Balizada pela convergência midiática, esta pesquisa demonstra como o receptor tem atuado nas mídias digitais online e como a televisão pode aproveitar as particularidades dessa interação entre meios para promover a criação de conteúdo colaborativo, no qual o usuário de rede social pode interferir, influenciando diretamente o resultado do produto desenvolvido, se tornando um novo protagonista midiático. Ferramenta pouco utilizada pela produção de televisão que, vagarosamente, começa a adentrar a realidade virtual, o forjamento desse novo processo de composição poderia não apenas entreter o receptor, como também enriquecer a linguagem e o conteúdo televisivos constantemente criticados. Este estudo expõe a influência do meio televisivo no que é discutido online; trata da postura ainda tímida do usuário na produção de conteúdos; e aborda as potencialidades das redes sociais enquanto canal de comunicação entre receptores e produtores. Este artigo se estrutura a partir da definição de rede social; além estudar que tipo de diálogo entre esse meio online e TV é praticada nos dias de hoje. Por fim, debate-se se a potencialidade da interação entre TV e redes sociais é utilizada em sua plenitude.
Keywords: Collaborative content; Television; Internet; Social networks; Conteúdo colaborativo; Televisão; Internet; Redes sociais